The Boundaries of Librarians’ and Pharmacists’ Expertise: Defining What it is to be Professional - Schindel, Theresa J.; Hicks, Deborah (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2019)
This paper explores findings from two separate studies to begin a conversation about how the concept of expertise, or boundaries defining professional knowledge and action, can be challenged or extended to better understand professionals’ roles, identities, and contribute most effectively to society. The first study examined the identity construction of librarians and the second study examined how pharmacists’ made sense of their prescribing roles. Expertise was central to both professions’ understanding of themselves and their professional roles.